Effect of atorvastatin on clinical manifestations of gout comorbid with arterial hypertension - Zolotariova, Natalya; Romanchenko, Maksym (ScienceRise: Medical Science, 2017)
Aim of the work was to determine a possible effect of atorvastatin on clinical symptoms of gout, comorbid with arterial hypertension. Materials and methods: 56 patients of middle age with gout and arterial hypertension were divided in groups of the standard treatment (n=26) and one with additional atorvastatin in 20 mg/day (n=30), the observation period was 43±9 days. Results: There were observed the significant decrease of hyperemia of injured articulations (р=0,03 for metatarsophalangeal articulations), insignificant decrease of the circle (р=0,17), increase of motility of involved articulations (р=0,19), compared with the control group, and wasn’t revealed any influence on the pain intensity by VAS and on clinical manifestations of arterial hypertension or office arterial pressure. Conclusion: atorvastatin addition to the standard gout therapy and arterial hypertension has the moderate anti-inflammatory effect, without influencing the pain intensity, arterial pressure and clinical manifestations of arterial hypertension